Community-engaged strategies to promote hepatitis B testing and linkage to care in immigrants of Florida. Issue 4 (December 2016) - Stanford, Jevetta; Biba, Alma; Khubchandani, Jagdish; Webb, Fern; Rathore, Mobeen H.
Abstract: To improve early identification and linkage to treatment and preventive services for hepatitis B virus (HBV) in persons born in countries with intermediate or high (>2%) HBV prevalence, the University of Florida Center for HIV/AIDS Research, Education, and Services (UF CARES) employed community-engaged strategies to implement the Hepatitis B Awareness and Service Linkage (HBASL) program. In this brief report, we present a summary of program components, challenges, and successes. Faith and community-based networks were established to improve HBV testing and screening and to increase foreign born nationals (FBNs) access to HBV care. A total of 1516 FBNs were tested and screened for hepatitis B. The majority were females (50.4%), Asians (62.8%), non-Hispanic (87.2%), and they also received post-test counseling (54.8%). Noted program advantages included the development of community networks and outreach to a large population of FBNs. The major challenges were institutional delays, pressures related to meeting program deliverables, and diversity within FBNs populations. Community health workers in the United States can replicate this program in their respective communities and ensure success by maintaining a strong community presence, establishing partnerships and linkage processes, developing a sustainability plan, and ensuring the presence of dedicated program staff.